Understanding Astronomy: Characteristics Of Celestial Bodies As Knowledge In Science Learning - Dhinda Anggita Prameswari; Umi Karimah; Elysa Putri Novitasari; Wahyu Kurniawati (Sean Institute, 2024)
This research aims to provide an understanding of astronomy, specifically the celestial bodies studied in science material. The method used in this research is a descriptive method. Celestial bodies are usually also called astronomical objects, celestial bodies are objects in the sky that can be seen from the earth. There are many types of objects in the sky such as the sun, moon and stars. In science lessons we study astronomy, one of which is about celestial bodies. By studying celestial bodies we can find out about various kinds of objects in the sky. From the results of the research we can understand about astronomy, specifically celestial bodies.